PROPOSAL OF THE MODEL OF RADICAL SPORTS INNOVATION IN THE FUNCTION OF DEVELOPMENT OF DEMOCRATIC SOCIETY AND ECONOMY (Heritage, 2022)
Sport in the function of general globalization of society at all levels of decision-making and all its segments is an unavoidable part of progress that directly affects technological development, culture, health, living standards, prestige, competitive supremacy of national economy and culture, respecting modern methods of groups and individuals to which partial interventions are economically unprofitable. Radical innovation is a long-term process that is vertically projected from the lowest to the highest level, respecting the latest technological advances, world standards and norms of strategic planning, staffing, dispersion, lobbying, competitiveness, market size and quality control of products and services. In cases of sudden disruption of the entire system and imbalance at the global level when recovery deadlines are not sufficient, extremely radical measures are introduced in order to stop negative tendencies. These measures are limited in scope and most often relate to alarming conditions caused by wars or natural disasters, and in the last two years caused by the epidemic and pandemic of the Corona virus, which first appeared in Wuhan, China in December 2019. The Chinese government declared a "state of emergency" on January 20, 2020. China managed to end the impact of the epidemic in a short time with measures such as curfew, work from home, mandatory wearing of masks when leaving home and shopping, wearing protective clothing, which even applied to pets. However, the policies pursued by countries against corona viruses differed (Ozturk, B., 2021, p:54).As can be seen, the corona virus is one of the most severe epidemics in human history. None of the epidemic diseases such as SARS and Ebola that people have experienced in modern times has threatened to cause a change in the world order. Although there are many claims, assumptions, and conspiracy theories regarding each stage, such as the occurrence, spread, and consequences of corona viruses, another important question is whether scientific data are consistent and systematic (Ozturk, B., 2021, p:54). Due to the deadly and respiratory virus that is spreading around the world, people are under great stress and their psychology is negatively affected by isolation and existential fears that are only an addition to life's worries (Ozturk, B., 2021, p:56). Such processes require urgent intervention and modulation of temporary measures that do not tolerate the democratization of the decision-making process and are based exclusively on the discourse of adapting to the new situation and require rapid transformation. Interventionism in such extremely radical modulation can be structural and / or commercial in nature as both contain quantum qualifications, creative and innovative elements of sport development and are found in education, public health and cultural fields. Recognizing multiculturalism as cultural pluralism with national signs, through the expansion of sports and sports competitions as its emphasized components, globalization is rapidly expanding to modernize processes and becomes a paradigm and model for other segments of society as a whole.
Keywords: sport, globalization, society, Corona virus, radical innovation